صراع اللسان العربي بين المستعمر ورجال الإصلاح في الجنوب الشرقي الجزائري - نماذج مختارة - بن عون, محمد الحاكم; العايبي, محمد (University of Eloued جامعة الوادي, 2022)
يمثل لسان كل مجتمع الخيط الناظم لتاريخه وهويته وإرثه الحضاري، وما إن يضعف هذا الخيط أو تمسّه عاديات الزمن، حتى تتسع الهوة بين المجتمع وإرثه الحضاري وتظهر القطيعة بينه وبين قيمه التي يتميز بها، ونتيجة تلك القطيعة، يبدأ بعد ذلك في اكتساب قيم دخيلة عن إرث مجتمعه، ولا تمت إلى قيمه الممسوخة بصلة، مما ينجر عنه مجتمع متعدد القيم رغم وحدة أصله. من هذا المنطلق عمل المستعمر الفرنسي في بلاد المغرب العربي بشكل عام وفي الجزائر بشكل خاص على طمس الهوية الحضارية للشعب الجزائري، وإنتاج مجتمع جديد بقيم جديدة، وبما أن اللسان العربي هو الرافد الأساسي للحضارة والفكر الجزائري، فقد عمل المستدمر الفرنسي على إضعافه ثم إحلال لغته -الفرنسية- محلها لتكوين جيل من المؤمنين بالفكر الغربي، غير أن الشعب الجزائري بقي صامدا متصديا لهذه السياسة، متمسكا بلغته وعروبته، ويتجلى ذلك من خلال المقاومة الثقافية التي حاولت الحفاظ على الإرث الثقافي في المساجد والزوايا والكتاتيب، ومع مطلع القرن العشرين برز رجال الإصلاح الذي ضحوا بالنفس والنفيس من أجل الحفاظ على هوية بلادهم الجزائر العربية المسلمة، ومن بين هؤلاء الشيخين محمد الأمين العمودي ومحمد الأخضر السائحي. وتتلخص أهمية هذا البحث في نقطتين أساسيتين أولاهما تتعلق بكشف القطيعة الحضارية التي حاول الاستعمار الفرنسي خطّها لإبعاد الجزائري المسلم عن حضارته وقيَّمه، أما الثانية فتتمثل في إبراز دور رجال الإصلاح في الجنوب الشرقي الجزائري الذين دافعوا عن اللسان العربي، لادراكهم بأن المسلمين وحّدهم الدين ورابطهم هو اللسان العربي الذي لا يصِحُّ الإسلام إلا به. Summary: The tongue of every society represents the thread that organizes its history, identity and cultural heritage. his society, and it has nothing to do with its distorted values, which leads to a multi-valued society despite the unity of its origin. From this standpoint, the French colonizer in the countries of the Maghreb in general and in Algeria in particular worked to obliterate the civilizational identity of the Algerian people, and to produce a new society with new values, and since the Arabic tongue is the main tributary of Algerian civilization and thought, the French colonizer worked to weaken it and then replace its language - French - its place to form a generation of believers in Western thought. However, the Algerian people remained steadfast in confronting this policy, adhering to their language and Arabism, and this is evidenced by the cultural resistance that tried to preserve the cultural heritage in mosques, corners and schools, and with the beginning of the twentieth century, the reform men who sacrificed With self and precious in order to preserve the identity of their country, Arab and Muslim Algeria, and among these two sheikhs, Muhammad Al-Amin Al-Amoudi and Muhammad Al-Akhdar Al-Saihi. The importance of this research is summarized in two main points, the first of which relates to revealing the civilizational estrangement that the French colonialism tried to line to distance the Algerian Muslim from his civilization and values. The Arab who is not correct Islam without him.
The struggle of the Arabic tongue between the colonizer and the reform men in the southeast of Algeria - selected models
مداخلة
Keywords: اللسان، العربي، المستعمر، الفرنسي، رجال، الإصلاح; the tongue, the Arab, the colonizer, the Guernsey, men, the reform